Caveat Translator: Understanding the Legal Consequences of Errors in Professional Translation - Byrne, Jody (The Journal of Specialised Translation, 2007)
At the very heart of translation studies is the issue of translation quality. Yet, while there are numerous methods for assessing the quality of translations, little is known about what happens when a translator produces a bad translation. This paper will show that translation error, as a whole, can have significant consequences for both translator and client and by examining a number of case studies gathered from official reports and communications, court records, newspaper articles and books it will illustrate the diversity of situations which can arise as a result of translation errors. The paper will then examine the issues of liability and negligence to illustrate the legal means by which translators can be held accountable for the quality of their work. By understanding how liability for faulty translations arises, it will be possible to see the implications of laws and directives governing technical translations which are subsequently examined. This paper examines specific legal requirements relating to technical translation and discusses the consequences of translation errors using specific case studies relating to technical translation.